Continuous Exposure to Ethylene Differentially Affects Senescence in Receptacle and Achene Tissues in Strawberry Fruit - Tosetti, Roberta; Elmi, Fardusa; Pradas, Inmaculada; Cools, Katherine; Terry, Leon A. (Frontiers in Plant Science, 2020)
Strawberry shelf life is limited, and little is known about the postharvest regulation of senescence in different fruit tissues. Strawberry is classified as a non-climacteric fruit, yet it is known that ethylene affects strawberry ripening. Here the effects of continuous exogenous ethylene (50 µL L-1) were investigated in cold stored strawberry (5° C). The physiological and biochemical responses of ripe strawberry were evaluated across six days, together with hormonal profiles of the whole fruit and individual tissues (achenes and receptacle). Continuous exposure to ethylene induced as a first response an accumulation of abscisic acid (ABA) in the receptacle tissue, followed by an increase in CO2 production. Ethylene also elicited sucrose hydrolysis and malic acid catabolism, with the major effect seen after 4 days of ethylene exposure. Additionally, accumulation of phenolics (epicatechin and chlorogenic acid) were also observed in ethylene treated strawberry. Achenes did not exhibit a response to ethylene, yet catabolism of both ABA and auxins increased by two thirds during air storage. In contrast, ethylene induced ABA accumulation in the receptacle tissue without ABA catabolism being affected. This hormonal disequilibrium in response to ethylene between the two tissues was maintained during storage, and therefore might be the precursor for the following biochemical variations reported during storage.